1998
DOI: 10.1093/molehr/4.11.1045
|View full text |Cite
|
Sign up to set email alerts
|

Expression of progesterone receptor isoforms in corpora lutea of human subjects: correlation with serum oestrogen and progesterone concentrations

Abstract: To understand the biological significance of progesterone receptor forms A (PR-A) and B (PR-B) in human corpus luteum, the expression of mRNA and serum steroid hormone concentrations were determined simultaneously in the luteal stages. The expression of PR-A mRNA predominated over PR-B mRNA in all samples analysed. Total PR (PR-AB) and PR-B mRNA concentrations at the late secretory phase were significantly (P < 0.01) lower than those at the early and mid secretory phases of the menstrual cycle. The ratio of PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 38 publications
3
18
1
Order By: Relevance
“…In the non-human primate, PR A levels decreased throughout the luteal phase while PR B remained unchanged . However, in the human corpus luteum, both PR A and PR B isoforms were reduced in the late-luteal phase (Misao et al 1998). Certainly the pattern of PR B expression in luteinised granulosa cells is similar to that of PR A/B in our experiments.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the non-human primate, PR A levels decreased throughout the luteal phase while PR B remained unchanged . However, in the human corpus luteum, both PR A and PR B isoforms were reduced in the late-luteal phase (Misao et al 1998). Certainly the pattern of PR B expression in luteinised granulosa cells is similar to that of PR A/B in our experiments.…”
Section: Discussionsupporting
confidence: 78%
“…In the primate corpus luteum, Western blotting suggested that the major PR variant is the B isoform . In human corpora lutea, however, PR A/B mRNA was found in higher concentrations than PR B mRNA (Misao et al 1998, Ottander et al 2000 and PR A was confirmed to be higher using Western blotting (Misao et al 1998). It seems clear, however, that both PR isoforms are expressed in the corpus luteum.…”
Section: Discussionmentioning
confidence: 88%
“…P 4 mediates its actions via nuclear and membrane receptors (PGR and PGRMC1, PGRMC2 respectively). As shown in the present study, the expression of PGR dropped along with the development of porcine CL, similar to bovine CL (Misao et al 1998). Thus, it is likely that a negative regulatory loop exists between the intraluteal concentration of P 4 and expression of PGR in CL of cyclic pigs, as demonstrated in bovine CL (Misao et al 1998).…”
Section: Luteolysissupporting
confidence: 82%
“…In the primate corpus luteum, Western blotting suggested that PR-B is the major isoform (Duffy et al 1997). In contrast, in human corpora lutea PR-A was confirmed to be higher using Western blotting (Misao et al 1998). The impacts of these differences are not fully understood yet.…”
Section: Gpermentioning
confidence: 97%